Synovial cyst of the acromioclavicular joint with and without rotator cuff tear: A case series of two patients. (2020) - De Maio, Fernando; Di Marcantonio, Arianna; De Luna, Vincenzo; Caterini, Alessandro; Tresoldi, Ilaria; Farsetti, Pasquale
Highlights: The most common acromioclavicular joint cyst (AJC) is associated to a rotator cuff tear (type 2). MRI provides a correct diagnosis, even of the type of AJC. Type 1 AJC should be surgically treated by excision and resection of the lateral clavicle. Type 2 AJC could be surgically treated by reverse total shoulder replacement. Abstract: Introduction: Acromioclavicular joint cyst (AJC) is a very uncommon condition of the shoulder observed in elderly patients, caused by a degenerative acromioclavicular (AC) joint, frequently associated to a rotator cuff tendon tear. There are two possible cause for the cyst formation. We report two different cases of a AC synovial cyst, with and without rotator cuff tear. Presentation of cases: We report two cases, in patients aged respectively 80 and 77 years, with a very large AJC. In one case, the cyst was associated to a rotator cuff tear, while in the other case, the rotator cuff did not present any evident lesion. Both cysts were successfully surgical excised and a distal clavicle resection was performed. Discussion: AJC is a rare complication observed in degenerative AC joint and in the majority of cases is associated to a rotator cuff tear. The diagnosis may be made by ultrasound and conventional radiographic examination, although MRI of the shoulder is generally preferred as it allows to better identify the condition of the rotator cuff. Generally, local aspiration of the cyst and corticosteroid injection fails with recurrence of the cyst and surgically treatment is indicated, especially in painful cases. Conclusion: Painful AJC should be surgically treated by excision of the cyst associated to a lateral clavicle resection; when a symptomatic massive rotator cuff is present, a reverse total shoulder arthroplasty may be considered. However, in elderly patients, who have no discomfort, watchful waiting may be the treatment of choice.